(untitled) (Architecture Image Studies, 2025)
The issue of refugees, particularly Rohingya is very sensitive and important for Malaysia due to its involvement with this issue since the conflict started a decade ago. Malaysian government is one of the active entity in International stage who brought the Rohingya issues to United Nations (UN) and Organization of Islamic Countries (OIC). Malaysia is not only an outspoken player on this issue but it has also open its door to the Rohingya despite of having criticism and security concern. Although there are number of studies discuss the fact, impact or root cause of the problem, suggestion to the government and so on, there are lack of studies has been done on the local Malaysian community acceptance towards the Rohingya refugees. Therefore this study attempts to identify Kedah local community’s awareness on Rohingya in Malaysia by examining their responses towards this group of refugees. Kedah local community is chosen due to its strategic location as among the main gateways that Rohingya refugees could enter Malaysia and their presence could also be seen within the local community. This study will also analyze this local community hopes and expectations to the government in dealing with Rohingya refugees. The study adopts a qualitative research method to avail the objective and the data has been collected through primary and secondary sources. This study reveals that Kedah local community is fully aware on the Rohingya refugee issues. Generally, they show positive responses towards the Rohingya although most of them do aware about the potential security threat there. This study finally illustrates an overall acceptance of Rohingya in Malaysia by the majority of Kedah local community.